Penicillin-like mimotopes from autodisplayed Fv-antibody library inhibiting β-lactamase activity - Bae, Hyung Eun; Jung, Jaeyong; Sung, Jeong Soo; Kwon, Soonil; Kang, Min-Jung; Jose, Joachim; Pyun, Jae-Chul (Royal Society of Chemistry, 2025)
A penicillin-like mimotope was screened from an Fv-antibody library which had the inhibition activity of beta-lactamase. Fv-antibody indicated the variable region (VH) of the immunoglobulin G, which includes three complementarity determining regions (CDRs). The Fv-antibody library was then prepared by randomizing the complementarity determining region 3 (CDR3), and it was expressed on the outer membrane of E. coli. The penicillin-like mimotopes were screened from the Fv-antibody library using magnetic beads with an immobilized monoclonal anti-penicillin antibody. The screened mimotopes were expressed as soluble Fv-antibodies and were also synthesized into peptides (11-mer). The binding affinity (KD) of the expressed Fv-antibodies and synthesized peptides was estimated using SPR measurements. The beta-lactamase inhibition activity of the Fv-antibodies and synthetic peptides was estimated using colorimetry based on the formation of penicilloic acid. The penicillin-like mimotopes of the expressed Fv-antibodies and synthesized peptides were demonstrated to have beta-lactamase inhibition activity in the bacterial lysates. Finally, the docking analysis of beta-lactamase and the screened CDR3 sequences demonstrated that the screened CDR3 sequences were specifically bound to the binding sites of beta-lactamase.